Long-Term Optical Imaging and Spectroscopy Reveal Mechanisms Underlying the Intrinsic Signal and Stability of Cortical Maps in V1 of Behaving Monkeys - Shtoyerman, Eran (J Neurosci, 2000)
Explorations of learning and memory, other long-term plastic changes, and additional cognitive functions in the behaving primate brain would greatly benefit from the ability to image the functional architecture within the same patch of cortex, at the columnar level, for a long period of time. We developed methods for long-term optical imaging based on intrinsic signals and repeatedly visualized the same functional domains in behaving macaque cortex for a period extending over 1 year. Using optical imaging and imaging spectroscopy, we first explored the relationship between electrical activity and hemodynamic events in the awake behaving primate and compared it with anesthetized preparations. We found that, whereas the amplitude of the intrinsic signal was much larger in the awake animal, its temporal pattern was similar to that observed in the anesthetized animals. In both groups, deoxyhemoglobin concentration reached a peak 2–3 sec after stimulus onset. Furthermore, the early activity-dependent increase in deoxyhemoglobin concentration (the “initial dip”) was far more tightly colocalized with electrical activity than the delayed increase in oxyhemoglobin concentration, known to be associated with an increase in blood flow. The implications of these results for improvement of the spatial resolution of blood oxygenation level-dependent functional magnetic resonance imaging are discussed. After the characterization of the intrinsic signal in the behaving primate, we used this new imaging method to explore the stability of cortical maps in the macaque primary visual cortex. Functional maps of orientation and ocular dominance columns were found to be stable for a period longer than 1 year.